PENGARUH KOMIK ONLINE BERBASIS MEDIA SOSIAL UNTUK SOSIALISASI ANTI NARKOBA TERHADAP KARAKTER SISWA SEKOLAH DASAR - Rahmy Fadilla Irman; Adisti Yuliastrin; Rian Vebrianto (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
Substance misuse is a problem that frequently arises among teenagers, particularly among pupils in primary school. In elementary school, the teaching focuses primarily on increasing students' knowledge and abilities, with very little attention paid to the students' moral and ethical development. Thus, the erosion of students' moral fiber will result in the country's failure to produce productive citizens in the following generation. The goal of this research was to investigate the influence that reading comics online has on the personalities of elementary students. In this work, experimental research, specifically quasi-experimental research, is used. Researchers use a method called random sampling to decide the sample they will use. Students in grade four of elementary schools served as the population for the sample. The control and experimental classes each had 22 students. This study used a Likert-scale questionnaire. This study endeavor analyzed data using descriptive analysis, normality, paired sample t-tests, and SPSS 16-assisted homogeneity tests. The Sig. (2tailed) value of the paired sample t-test is 0.000<0.05, so Online Comic Learning Media does affect student character. The findings of this study imply that it is reasonable to expect teachers to be able to employ learning media that is both interesting and concrete, as well as to be accompanied by technology; one of the choices is making use of comics